2011
DOI: 10.1097/mpg.0b013e3182062fcc
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, AFABP, and Leptin in Human Breast Milk During 12 Months of Lactation

Abstract: All of the hormones were detectable in BM up to 12 months of lactation, with decreasing trend until M3 and subsequent increase till M12. We speculate that higher levels in M6 and M12 may be caused by longer intervals between breast-feeding due to the introduction of complementary food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 19 publications
9
52
3
2
Order By: Relevance
“…We obtained longitudinal data from breast milk samples starting in the first week including colostrum and transitional milk and ending with mature milk after 6 mo lactation. Our findings were supported by previous data about the presence of leptin in breast milk during the whole lactation period (1,2,6,18,(23)(24)(25)(26)(27)(28)(29)(30) and suggest that maternal leptin could regulate body weight gain during early infancy. We observed quite low, but nearly constant breast milk leptin levels over 6 mo with distinct interindividual differences.…”
Section: Discussionsupporting
confidence: 81%
“…We obtained longitudinal data from breast milk samples starting in the first week including colostrum and transitional milk and ending with mature milk after 6 mo lactation. Our findings were supported by previous data about the presence of leptin in breast milk during the whole lactation period (1,2,6,18,(23)(24)(25)(26)(27)(28)(29)(30) and suggest that maternal leptin could regulate body weight gain during early infancy. We observed quite low, but nearly constant breast milk leptin levels over 6 mo with distinct interindividual differences.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, earlier human studies reported either unchanged (Bronsky et al, 2011) or Figure 1. Plasma adiponectin concentration (μg/mL) in cows (n = 50) during the experimental period 1 (from wk 3 antepartum to wk 12 postpartum), period 2 (3 wk of feed restriction, starting at about 100 DIM), and period 3 (8 wk of realimentation).…”
contrasting
confidence: 41%
“…The mean adiponectin concentration of 35.0 ng/ml was slightly higher than previously reported milk concentrations at 1 year of lactation of 25.7 ± 1.4 ng/ml [21]. Adiponectin receptor 1 was detected in rodent small intestine, which might facilitate the absorption of milk adiponectin and thus have the appetite-enhancing effect of high milk adiponectin levels [22].…”
Section: Resultsmentioning
confidence: 66%